India - Development and Growth in Northeast India : The Natural Resources, Water, and Environment Nexus - World Bank (Washington, DC, 2012)
India's Northeastern Region consists of eight states -- Arunachal Pradesh, Assam, Manipur, Meghalaya, Mizoram, Nagaland, Sikkim, and Tripura -- occupying 262,179 square kilometers and with a population of 39 million (2001 census). This report has come about at the request of the Indian Government for the World Bank to focus more of its attention on the Northeastern Region in order to support poverty reduction and development in the region. Accordingly, the Ministry of Development of North Eastern Region (MoDONER) and the Bank devised a study that would provide a broad, regionwide view. This report synthesizes the study, which focuses on water and forests, two key interconnected resources of the region, and the institutional framework that deals with their management. This paper includes the following headings: introduction; objective, process, audience, and scope of this study; the Northeast Region -- water and forest resources; institutional environment; key findings of the study; challenges for the Northeast Region; recommendations for priority activities, and conclusions.